Penggunaan Metode Game Development Life Cycle (GDLC) Untuk Memudahkan Belajar Bahasa Inggris Dalam Media Game - Rijal Agus Rusmana; Asriyanik Asriyanik; Iwan Rizal Setiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of information and communication technology has developed rapidly in various fields such as in the field of education and the field of play. Technology that is often used in all circles is a smartphone, the use of smartphones in addition to work can also be used to play. Ownership of smartphones according to the survey approximately 81.7% are used to send messages, regarding education, especially English learning according to the EF EPI survey (Englisg Profiency Index) Indonesia is in position 80 in Asia and includes low profiency. It can be concluded that there are still many Indonesian people, especially elementary school children, who still do not know about English. Therefore, a solution is made to introduce English with the theme of writing (writing) on game media, in making this educational game using the GDLC (game development life cycle) method. Educational games need development because many of the mechanics in educational games have passive mechanics, therefore in this game added mechanics, namely endless runner. After making the Tiny Man Genius game, tests were carried out on elementary school children in grades 4 and 6 based on the results of the pre-test and post-test conducted, it looks quite good even though in the pre-test session 81.3% were still below 100 with a maximum score of 200, but in the second experiment, the post-test increased, namely 93.8% increased and 87.5% with scores above 100. After conducting the test, the children stated that 68.8% helped in learning English.